Transformasi SDM: Dampak Peningkatan Kompetensi Digital dan Penerapan Budaya Agile terhadap Produktivitas Kerja di Sektor Elektronik Batam - Elbani, Iqrar; Riki (Program Studi Manajemen FEBM UMRAH, 2025)
This study aims to analyze the effect of digital competence and agile work culture on employee performance in the era of industrial transformation 4.0. The background of this research is driven by the phenomenon of technical skills gaps and cultural adaptation challenges in the electronic manufacturing sector in Batam City. The research method employed is quantitative, utilizing questionnaires distributed to 100 employees at the Batamindo Industrial Park. The data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with SmartPLS 3.0 software. The results indicate that: (1) Digital competence has a positive and significant effect on employee performance, and (2) Agile work culture has a positive and significant effect on employee performance. Simultaneously, both variables contribute an influence of 67.8% on employee performance. The conclusion of this study emphasizes that digital upskilling strategies combined with flexible cultural transformation are key determinants in increasing productivity in the modern manufacturing industry